PS02.186: EUS-GUIDED FIDUCIAL MARKER INSERTION TO GUIDE RADIOTHERAPY IN ADVANCED ESOPHAGEAL CARCINOMA. (14th September 2018) - Chan, Shannon; Teoh, Anthony; Chi Yip, Hon; Wong, Vivien; Chiu, Philip; Ng, Enders
Abstract: Background: The use of radiotherapy with or without concurrent chemotherapy is frequently required in treatment of advanced esophageal carcinomas. It can be given in an adjuvant, neoadjuvant or definitive setting. However, the margins of the tumor are often difficult to ascertain on computed tomography. Thus, EUS-guided fiducial marker insertion has an important role to aid the localization of the proximal and distal margins of the esophageal tumor. However, the optimal technique of the procedure is still uncertain. Methods: This was a retrospective study of all patients who received EUS-guided fiducial marker insertion between March 2015 and October 2017. All patients suffering from esophageal carcinoma scheduled for radiotherapy underwent the procedure within one week of the scheduled appointment. Gold fiducial markers 5mm x 0.35mm (Visicoil, IBA Dosimetry, USA) were back loaded onto a 22-gauge needle (Vizishot, Olympus Medical, Japan) or (Expect, Boston Scientific, USA). The markers were placed under EUS guidance either intratumorally or in the normal submucosa just proximal and distal to the tumor.The submucosal planes were raised with diluted hyaluronic acid before insertion of the marker. Outcome parameters included tumor characteristics, early and late migration rates and tumor response rates. Results: 35 patients were included in the study. The mean (S.D.) age was 61.0 (9.9) years old. The mean (S.D.) length of the tumor were 7.2 (6.0) cm and and 86.2% of the patients had stage 3 disease. 27 patients had markers inserted by EBUS and 71.4% in the submucosa. When comparing fiducials that were placed in the submucosa versus intratumorally, significantly more fiducials had early (30% vs 0%, P  = 0.004) and late migration (80% vs 0%, P  < 0.001) in the intratumoral group. There were no differences in the stage of disease ( P  = 0.870), percentage of patients that completed radiotherapy ( P  = 0.063) and response rate ( P  = 0.197). There were no adverse effects in both groups. Conclusion: In esophageal carcinomas planned for radiotherapy, EUS-guided fiducial markers should be placed in the submucosa just proximal and distal to the tumor instead of intratumorally. This may be able to increase the precision for radiotherapy. Disclosure: All authors have declared no conflicts of interest.